Role of topo-geographical conditions of Northern Central Region Vietnam and the difference of heavy rains between North and South Ngang Pass - Van, Nguyen Khanh (Vietnam Journal of Earth Sciences, 2012)
Following the article “Causes and the occurring rule of heavy rain unusual heavy rain” in North Central of Vietnam [Journal of Sciences of the Earth T.31, N°3/2009], this paper will present the reseach results of the resonant impacts of topo-geographic conditions in difference of heavy rains between North and South Ngang Pass.Base on the weather situation maps, daily rainfall data over North Central territory (1987-2006), frequencies of heavy rains occurrence corresponding to 7 types of Synoptic Weather Situation (SWS) - major factor leading to heavy rain - have been analyzed and evaluated. The results of analysing simultaneously topo-geographic conditions of NNP (Northern Ngang Pass) and SNP (Sourthen Ngang Pass) territories together with SWS show that:- For the heavy rain caused purely by cold air mass (CAM): in NNP, there are only 7 waves (equivalent 10.4% of total number of SWS), while in SNP, there are 41 waves (occupied 37% of total number of SWS).- For the heavy rain caused by CAM and combination of CAM and other SWS: in NNP, there are 8 waves (11.9% of total number of SWS), while in SNP, 51 waves (accounts for 45,9%).- The differences in topo-geographic condition of SNP, especially the directions of mountain ranges, characteristics of major mountain ranges, as well as the directions of coast line, are the main reason leading to the increasing convergence and increasing the number ofheavy rains clearly.- The study of heavy rains and topo-geographical conditions will be a source of valuable information, contributing to more precisely forecast of heavy rains in the areas of Northern Central Region of VietnamThe above approach of geographic climatology to examine the topo-geographical conditions and heavy rains is a new andreasonable approach. It allows to solve the natural disaster problem more effective and more useful. This special approach can be appliedto similar researches in areas of Southern Central Region of Vietnam.